THE EFFECT OF FINANCIAL LITERATION IMPLEMENTATION ON THE PERFORMANCE OF FINANCIAL MANAGEMENT IN MIDDLE SMALL MICRO ENTERPRISES IN TOMOHON CITY - Untu, Victoria N. (Archives of Business Research, 2021)
The research that will be carried out by the team refers to one of the Higher Education Research Master Plans, in this case Sam Ratulangi University, which is about matters related to the social, humanities and culture fields, with the topic of increasing the competitiveness of MSMEs and cooperatives. In this 21st century, the ability to manage money and finances effectively is becoming increasingly important, not only for professionals but for everyone who is responsible for managing financial affairs in everyday life. This ability is included in the term financial literacy. Financial literacy is not limited to understanding knowledge, skills and beliefs of existing financial institutions, products and services, but attitudes and behavior also have an influence in increasing financial literacy for the realization of public welfare. This study aims to determine how much influence the implementation of financial literacy has on financial management for MSME actors in Tomohon City. As for the sample in this study are the 70 micro, small and medium enterprises in Tomohon city. The final result or output of this research is in the form of a study on the implementation of good financial literacy in financial management performance in micro, small and medium enterprises in Tomohon city In addition, what is also the outcome of this research is the publication of National and International Journals. Keywords: financial literacy, financial management, MSMEs